인공고관절용 세라믹골두의 안전성평가 - 김대준; 김신윤; 최헌진 (한국생체재료학회, 2003)
Ceramics have been utilized as a material for replacement of metal artificial femoral heads to achieve a longevity of total hip replacements. For this purpose ceramics should possess both high mechanical properties and high reliability in the human environment. Even though many researches were engaged in improvement of mechanical properties of ceramics and investigation of wear behaviors of the materials, no systematic effort has been exerted to evaluate the ceramic femoral heads for safe clinical applications. The present review deals with the evaluations of the mechanical properties, such as flexural, compressive, and fatigue strengths and wear resistance, surface roughness and sphericity of the femoral heads, and biocompatibility required for reliable clinical applications of the ceramic femoral heads.